Labor Market Advantages of Organizational Status: A Study of Lateral Partner Hiring by Large U.S. Law Firms - Rider, Christopher I.; Tan, David (Organization Science, 2015)
Prior research demonstrates product market advantages of organizational status but largely neglects factor market advantages. We propose that status is advantageous in labor markets because individuals generally consider employer status a nonpecuniary employment benefit. Dyadic analyses of lateral partner hiring by large U.S. law firms demonstrate two status-based advantages in employee hiring and retention. First, high-status firms are more likely than low-status ones to hire an employee from a more profitable competitor. Second, high-status firms are most likely to lose an employee to a lower-status competitor when the competitor is—atypically—more profitable. We discuss implications of these findings for individual and organizational status attainment and for the stability of industry status hierarchies.